Técnicas de gamification como auxílio ao ensino da disciplina redes de computadores - SILVA, Gabriel Medeiros da (2020)
The technological breakthrough has brought to the classroom students presenting a new profile, called digital natives, their way of learning is different, challenging the teacher to find new ways of engaging the student when teaching the discipline. Faced with this challenge this work intended to help graduate students training in computer science and information systems, improving their learning experience and their performance at the discipline of computer networks. The objective of the work is to develop a miscellany of quiz game, to select and to evaluate three tools that serve as framework for the proposed study, these three auxiliary tools should help fixing and reviewing the content taught by the teacher in the computer networks discipline, hoping that they are an innovative way of teaching the subject and instigating motivation and interest from the students. The research method used is an analysis of the literature on technology and education, computer networks and gamification. Therefore, some quiz games tolls will be analyzed succinctly and, among them, three will be selected to be applied practically at classrooms, the impressions about the tools will be collected through questionnaires created specifically for this context, where the student’s motivation, his experience regarding the application and the level of learning are evaluated. Then, the results will be evaluated and compared. It is expected that the application of the quiz games from this work improves the student's learning experience, reviewing and reinforcing the concepts learned in a fun and innovative way, offering an effective alternative of learning that makes a difference in the formation of a professional in the computing area.